Open Microdiscectomy or Tubular Discectomy: What Is Better for Lumbar Disc Herniation - Gupta, Sajag Kumar; Faheem, Mohd (Nepal Journal of Neuroscience, 2023)
Introduction: Many different minimally invasive procedures can be used to treat lumbar disc herniation. In the management of lumbar disc herniation, Open microdiscectomy MD is the gold standard and is used as a benchmark for comparison with more recent techniques like tubular discectomy. The purpose of this study was to assess the complication rates of tubular discectomy and to compare the postoperative outcomes of individuals undergoing tubular discectomy with those undergoing MD. Material & Methods: A retrospective analysis of 250 patients who underwent single-level lumbar discectomy either by tubular TD or MD between JULY 2018- JUNE 2023 was performed. The differences in the 2 groups’ demographics, surgical length, intraoperative blood loss, overall hospital stay, pain score on the visual analogue scale (VAS), Oswestry Disability Index (ODI) score both before and after the procedure, and complications were assessed. Results: Out of the 250 patients, 130 patients were treated with MD and 120 by tubular discectomy TD. The mean age in MD and tubular TD group was 45.5 and 45.8 years. There was a improvement in VAS and ODI scores at 4 weeks in both the groups. There was a greater reduction of back pain in the TD group at 2 weeks compared to MD group but at 1 month both are comparable. Average surgical time was shorter in MD (71.6 min) as compared to TD group (80.2 min). the Average blood loss was higher (90.2 mL) in MD group as compared to TD group (35.8 mL) (Table 3 ). Length of incision as measured from the surgical scar was 1.7 cm in TD while it was 3.0 cm in MD group. Average hospital length of stay in TD (1.2 days) which was less than MD group (2.1 days). Likewise, MD group patients took 5.9 weeks to return to activity which was higher than the TD group (4.1 weeks). There were 9 cases (6.9%) of dural tear in MD and 10 cases (8.3%) in TD group. Conclusion: Sciatica caused by disc herniation can be effectively and safely treated with lumbar discectomy, whether it is TD or MD. In comparison to MD, the TD method for treating symptomatic lumbar radiculopathy is superior in that it causes less postoperative back pain, less blood loss, a shorter hospital stay, and a quicker return to work. Despite the learning curve, TD has been demonstrated to be a viable choice for treating lumbar disc herniation in patients who are carefully chosen.